Pengaruh celebrity endorsement dan social media marketing terhadap purchase decision dengan brand image sebagai variabel intervening - Azizah, Rizka Nur; Fadhilah, Muinah; Cahyani, Putri Dwi (Entrepreneurship Bisnis Manajemen Akuntansi (E-BISMA), 2024)
This study aims to determine the effect of Celebrity Endorsement and Social Media Marketing on Purchase Decision with Brand Image as an intervening variable on scarlett whitening users in Yogyakarta. This study uses a quantitative research method, with a purposive sampling technique. The sample in this study was 112 respondents who were scarlett whitening users in Yogyakarta. The data collection method used a questionnaire via google form. The data analysis technique used data quality testing, classical assumption testing, hypothesis testing and sobel tests through the help of the SPSS program. The results of this study indicate that Celebrity Endorsement has a positive and significant effect on Purchase Decision. Social Media Marketing has a positive and significant effect on Purchase Decision. Celebrity Endorsement has a positive and significant effect on Brand Image Social Media Marketing has a positive and significant effect on Brand Image Brand Image has a positive and significant effect on Purchase Decision Brand image is able to mediate Celebrity Endorsement on Purchase Decision. Brand image is able to mediate Social Media Marketing on Purchase Decision. The findings of this study can provide Scarlett Whitening with in-depth insights into consumer preferences as well as the latest market trends, so that companies can develop more relevant and effective marketing strategies. In addition, the results of this research can also be used to strengthen the brand image by highlighting values that are in accordance with consumer needs and expectations.